CONTEXTUAL TEACHING AND LEARNING APPROACH TO TEACHING WRITING - Satriani, Intan; Emilia, Emi; Gunawan, Handi (Indonesian Journal of Applied Linguistics, 2012)
Abstract: This article reports a study on the implementation of contextual teaching and learning approach to teaching English writing to second graders of a Junior High Shool in Bandung. The study aims to investigate the strategies of Contextual Teaching and Learning (CTL) (as adapted from Crawford, 2001) and the advantages of using CTL approach. The study employed a qualitative case study research design. The data were obtained from several instruments, namely class observations, students’ interview and students’ writing products which were then analyzed using writing assessment criteria taken from Rose (2007, as cited by Emilia, 2011, p. 151). The findings revealed that the teaching writing program was successful to improve students’ recount writing skill. Specifically, they showed some improvement on schematic structure, grammar roles, and graphic features. Moreover, the data from observation, interview, and documentation of students’ text showed some benefits of CTL. These include: (1) engaging students in the writing activity; (2) increasing students’ motivation to participate actively in the writing class; (3) helping students to construct their writing; (4) helping students to solve their problems; (5) providing ways for students to discuss or interact with their friends; and (6) helping the students to summarize and reflect the lesson. Based on these findings, it is recommended that CTL be implemented in teaching writing.   Keywords: contextual teaching and learning, teaching writing